2021
DOI: 10.3390/ma14082068
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Autogenous Self-Sealing of Mortar: Influence of Curing Condition

Abstract: With the construction of projects under severe environments, new and higher requirements are put forward for the properties of concrete, especially the autogenous self-sealing property, which is greatly affected by the curing environment and the state of the water. Herein, six types of curing conditions, including in air with a relative humidity of 30%, 60%, and 95%; flowing water; wet-dry cycles; and static water, are designed to investigate the autogenous self-sealing of mortar under different curing conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To improve and obtain a remarkable self-healing ability in concrete, numerous studies have been conducted based on healing conditions and alternative cementitious materials. Yuan et al [8,9] found that the self-sealing ratios in the static liquid water environment were higher than in other environments, including in air with various humidity, flowing water, and wet-dry cycles. They also noted that cement containing more 30-60 nm cement particles in mortar had a better self-healing ability in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…To improve and obtain a remarkable self-healing ability in concrete, numerous studies have been conducted based on healing conditions and alternative cementitious materials. Yuan et al [8,9] found that the self-sealing ratios in the static liquid water environment were higher than in other environments, including in air with various humidity, flowing water, and wet-dry cycles. They also noted that cement containing more 30-60 nm cement particles in mortar had a better self-healing ability in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…These hydration products, depending on various gravitational forces to overlap and bind, form a cement structure with a certain strength. The added retarder can postpone the rate of cement hydration products absorbing and condensing into a continuous reticular flocculation structure, postpone the cement hydration reaction and extend the concrete setting time, and make the fresh concrete maintain not only plasticity but also other properties over a longer period [ 2 , 3 ]. Currently, the commonly used retarders include small molecule sugar, inorganic boric acid (inorganic borate), organic lignosulfonate and its derivatives, hydroxycarboxylic acid (hydroxy carboxylate), etc.…”
Section: Introductionmentioning
confidence: 99%